2012
DOI: 10.4304/tpls.2.12.2471-2477
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Cameroon Francophone English (CamFE) Phonology

Abstract: Abstract-This paper analyses some aspects of English pronunciation of French-Speaking Cameroonians termed Cameroon Francophone English (CamFE) to show that this variety of New Englishes has stable features. The data come from the oral reading of some selected words and sentences (see the appendix) by 50 French-speaking Cameroonian subjects of different levels of education, radio broadcasts ( especially Morning Safari 1 ), TV debates, political speeches, casual conversations and seminar sessions.The focus is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…They comprise the nasal vowels / E) , A) , ç) / which are not attested in RP (Received Pronunciation) but in French. This feature of CamFE is quite stable, and has been identified by a number of previous studies (Safotso 2001(Safotso , 2006(Safotso , 2012(Safotso , 2015Kouega 2008). Those studies mostly identified the feature without getting into an in-depth analysis of its working processes.…”
Section: Vowel Nasalization Processes In Cameroon Francophone Englishsupporting
confidence: 59%
See 2 more Smart Citations
“…They comprise the nasal vowels / E) , A) , ç) / which are not attested in RP (Received Pronunciation) but in French. This feature of CamFE is quite stable, and has been identified by a number of previous studies (Safotso 2001(Safotso , 2006(Safotso , 2012(Safotso , 2015Kouega 2008). Those studies mostly identified the feature without getting into an in-depth analysis of its working processes.…”
Section: Vowel Nasalization Processes In Cameroon Francophone Englishsupporting
confidence: 59%
“…The data analysed partly come from past studies (Safotso 2001(Safotso , 2006(Safotso , 2012(Safotso , 2015Kouega 2008) and from the oral reading of some test words by some Frenchspeaking undergraduate/ postgraduate students of the…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few researchers (Abang, 2000;Kouega, 2009;2013;Ombouda Onana, 2010;Khan, 2012;Tagne Safotso, 2012 to name only these) have examined the vowel system of the English of francophones in Cameroon, contrasting it with that of RP English. A total of 24 oral vowels and six nasal ones were thus identified.…”
Section: Introductionmentioning
confidence: 99%
“…In CamE, Masanga (1983), Mbangwana (1987), andSimo Bobda (1994) report that consonant clusters simplification, reduction or the devoicing of some members of the cluster, and vowel epenthesis are stable features. Tagne Safotso (2012Safotso ( : 2473 observes that the dropping of the last member of the cluster is very frequent in CamFE , e.g. told, went, landlord .…”
Section: Mutual Intelligibility On Consonant Clustersmentioning
confidence: 99%